Islamic Harmony Examplar: The Qur'an's Frame on Social Interaction with Non-Muslims - M. Ilham; Muhammad Majdy Amiruddin; Arifuddin Arif (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2020)
The actual dynamic authenticity of social life often shows accusations that religion is a source of social friction, violence, or conflict. The spirit of the Koran shows an appreciative attitude, even inviting to the meeting point (common platform) of monotheism (tauhid) which is the basic teaching of the Torah, the Bible, and the Koran. This paper aims to explore the existence of non-Muslims from the perspective of the Koran, the variants, and principles of social harmony with them. This paper uses qualitative as a method and literature as an approach. From the perspective of the Koran, there are 3 variants of arranged interactions. First in trade relations, second in marital relations, and third in political relations. The three variants of interaction must be based on the principle of Ihsan (good behavior) and Adalah (fair). Implications of this research present the idea of a meeting point between religions. This meeting point is expected to eliminate the friction of exclusivity between religious communities to create harmony and peace.